Political signalling and emissions trading schemes in China: Insights from Guangdong Province - XIANG, Chen (Institutional Knowledge at Singapore Management University, 2022)
China's approach to environmental regulation relies heavily on campaign-style enforcement and blunt-force regulation. While considered effective in the short run, this approach is often inefficient and generates unintended regulatory outcomes in the longer run. At the same time, China continues to experiment with the use of market-based approaches that are theoretically more efficient and have the potential to facilitate sustained reductions in carbon emissions. Arguably the most high-profile example is the Guangdong Emissions Trading Scheme (ETS), which was launched in 2013 as a national pilot scheme. We construct a synthetic control of Guangdong and analyse 51,076 party-led newspaper reports to show that while the ETS reduced emissions in the short run, these reductions were systematically associated with political signalling. Notably, emissions reduced substantially upon the announcement of the ETS in 2011 – a full two years before the scheme was scheduled to begin – before rebounding to near pre-ETS announcement levels by 2017. The presence of an anticipation effect and the systematic association between political signalling and emissions reductions mirrors findings on China's more direct approaches to environmental regulation. Our findings suggest that market-based mechanisms in China may not be qualitatively different from more direct forms of environmental regulation.